Experimental investigation of film pressure distribution in water-lubricated rubber journal bearings. (April 2014) - Geng, Tao; Meng, Qingfeng; Wang, Nan; Yuan, Xiaoyang; Meng, Qinghu; Jia, Qian
Measurements of lubricant film pressure were made on water-lubricated rubber journal bearings with eight axial grooves. For measuring full circumferential pressure of bearing, pressure transducers were mounted on the shaft of test rig. Pressure data were transferred by means of wireless data transmission while shaft rotating. Pressures under different axial positions of bearing were simultaneously measured by different transducers on shaft. Film pressures of bearing operated under different loads, shaft speeds and water supply pressures were compared and analyzed. Experimental results reveal the existence of negative pressure region in water-lubricated rubber bearing. The maximum negative pressure appears at the beginning of the divergent region of fluid film. Different operating conditions are indicated by the fluctuation range of film pressure. For every operating condition, the biggest pressure fluctuation occurs at the axial middle part of bearing. The changes of load and shaft speed have larger influence to film pressure amplitude than the change of water supply pressure within experimental range.